2015
DOI: 10.1111/rge.12065
|View full text |Cite
|
Sign up to set email alerts
|

Ore Genesis and Formation Age of the Gaogangshan Mo Deposit, Heilongjiang Province, NE China

Abstract: The Gaogangshan Mo deposit, located in the northern part of the Lesser Xing'an Range (the eastern part of the Xing'an-Mongolia Orogenic Belt), is one of the newly discovered Mo deposits in northeast China. Ore bodies occur in the granite and are generally in vein and stockwork forms. Major metallic minerals in the ore include pyrite and molybdenite. The styles of mineralization are disseminated, veinlet-disseminated, and veinlet. The major types of wall-rock alteration are silicification-potassic alteration, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…Large Mo deposits such as Fu'anbu, Jide, Dashihe, and Daheishan, together with the Chang'anbu deposit, belong to the Lesser Xing'an Range–Zhangguangcai Range belts and have similar characteristics in terms of metallogenesis and mineralization. Re–Os ages of molybdenites from the Daheishan and Dashihe deposits are 186.7 ± 5.0 and 168.2 ± 3.2 Ma, respectively, consistent with the emplacement of adamellite of the Fu'anbu deposit at 170 Ma (Chen et al, ; Hao et al, ; Wu, Jahn, Wilde, & Sun, ; Zhang et al, ). These consistent ages suggest that diagenesis and metallogenesis of the Chang'anbu deposit and other Mo deposits occurred during the early Yanshanian.…”
Section: Discussionsupporting
confidence: 60%
“…Large Mo deposits such as Fu'anbu, Jide, Dashihe, and Daheishan, together with the Chang'anbu deposit, belong to the Lesser Xing'an Range–Zhangguangcai Range belts and have similar characteristics in terms of metallogenesis and mineralization. Re–Os ages of molybdenites from the Daheishan and Dashihe deposits are 186.7 ± 5.0 and 168.2 ± 3.2 Ma, respectively, consistent with the emplacement of adamellite of the Fu'anbu deposit at 170 Ma (Chen et al, ; Hao et al, ; Wu, Jahn, Wilde, & Sun, ; Zhang et al, ). These consistent ages suggest that diagenesis and metallogenesis of the Chang'anbu deposit and other Mo deposits occurred during the early Yanshanian.…”
Section: Discussionsupporting
confidence: 60%
“…We imagine that a Jurassic stock may be under the Liushengdian intrusions and it is genetically related to the deposit; nevertheless, there is no proof or now discovery can demonstrate. More recently, Hao et al () reported a U–Pb isochron age of 259.9 ± 2.0 Ma for a granite porphyry of the Gaogangshan Mo deposit in the LXR, and Zhang () obtained a U–Pb age of 254.9 ± 3.1 Ma for a granodiorite of the Houdaomu Mo deposit in the MJP. In addition, Late Permian granitoids have also been recognized within the MJP in recent years, including the 248 Ma Dayushan, the 251 Ma Dahongshilazi, the 252 Ma Anyi, the 253 Ma Liushuhe, the 259 Ma Qingyang, the 253 Ma Erhedian, and the 252 Ma Balanhe plutons (Sun, Wu, & Gao, ; Wu et al, ; Zou, ).…”
Section: Discussionmentioning
confidence: 99%
“…The dominant regional structures are oriented either in the northeast direction or in the nearly north-south direction and include the Dunhua-Mishan fault, Yitong-Yilan fault and Jiayin-Mudanjiang fault. It is believed that the distributions of igneous rocks and deposits were controlled at large by these dominant regional structures [6,8,[39][40][41][42][43][44]. In the LXR, the representative deposits are (1) Cuiling, Gaosongshan, Luming and Huojihe porphyry Mo deposits; (2) Gaosongshan, Yongxin and Dong'anm epithermal gold deposits; and (3) Ergu, Baoshan and Cuihongshan skarn-hosted deposits.…”
Section: Geological Backgroundmentioning
confidence: 99%